Innovation Ecosystems against SARS-CoV Coronavirus: Pharmaceutical Industry - Chávez Angeles, Manuel Gerardo (Mercados y Negocios, 2021)
The article uses game theory to make a situational analysis of research and development (R&D) for treatments against the coronavirus SARS-CoV. The bioeconomic complexity causes a market failure with the virtual disappearance of the pharmaceutical industry. This requires government intervention for the implementation of a pharmaceutical industrial policy. The paper proposes the design and enactment of a National Pharmaceutical Policy (NPP) not based exclusively in the market. It proposed the creation of a National Academy of Mexican Traditional Medicine and the implementation of e-government solutions based on the Internet of Medical Things (IoMT)